solve x and y only by substitution method
Attachments:
![](https://hi-static.z-dn.net/files/dac/633aa1310135fc0080fd12e42dbd1036.jpg)
Answers
Answered by
0
Answer:
y=(b²-ab)/(a+b), x=(a²-ab)/(a+b)
Step-by-step explanation:
- x+y=a-b => x=a-b-y
- ax-by=a²-b²
- a(a-b-y)-by=a²-b² ---- substitute x
- a²-ab-ay-by=a²-b
- b²-ab=ay+by
- y(a+b)=b²-ab
- y=(b²-ab)/(a+b)
- x=a-b-y=a-b-(b²-ab)/(a+b) ---- substitute y
- x=((a-b)(a+b)+b²-ab)/(a+b)
- x=(a²-b²+b²-ab)/(a+b)
- x=(a²-ab)/(a+b)
Solved
Similar questions
Chemistry,
6 months ago
Math,
6 months ago
Social Sciences,
6 months ago
Physics,
1 year ago
Business Studies,
1 year ago
Economy,
1 year ago